Comparison of different medical treatments for primary hyperaldosteronism: a systematic review and network meta-analysis - Wen-Yu Ho; Ching-Chung Hsiao; Ping-Hsun Wu; Jui-Yi Chen; Yu-Kang Tu; Vin-Cent Wu; Jia-Jin Chen (Therapeutic Advances in Chronic Disease, 2024)
Background: The effectiveness and side effects between different medical treatments in patients with primary hyperaldosteronism have not been systematically studied. Objective: To analyze the efficacy between different mineralocorticoid receptor antagonists (MRAs) and epithelial sodium channel (ENaC) inhibitors in a network meta-analysis (NMA) framework, while also evaluating adverse events. Design: Systematic review and NMA. Data sources and methods: The systematic review and NMA was reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. PubMed, MEDLINE, the Cochrane library, and Excerpta Medica database (EMBASE) were searched for randomized controlled trials (RCTs) involving adult patients with primary hyperaldosteronism until 23 June 2023. Studies that compared the efficacy and side effects of different medical treatments of primary hyperaldosteronism were included. The primary outcomes included the effect on blood pressure, serum potassium, and major adverse cardiovascular events. The secondary outcomes were adverse events related to MRAs (hyperkalemia and gynecomastia). Frequentist NMA and pairwise meta-analysis were conducted. Results: A total of 5 RCTs comprising 392 participants were included. Eplerenone, esaxerenone, and amiloride were compared to spironolactone and demonstrated comparable effect on the reduction of systolic blood pressure. In comparison to spironolactone, eplerenone exhibited a less pronounced effect on reducing diastolic blood pressure [−4.63 mmHg; 95% confidence interval (CI): −8.87 to −0.40 mmHg] and correcting serum potassium (−0.2 mg/dL; 95% CI: −0.37 to −0.03 mg/dL). Spironolactone presented a higher risk of gynecomastia compared with eplerenone (relative risk: 4.69; 95% CI: 3.58–6.14). Conclusion: The present NMA indicated that the blood pressure reduction and potassium-correcting effects of the three MRAs may demonstrate marginal differences, with confidence levels in the evidence being very low. Therefore, further research is needed to explore the efficacy of these MRAs, especially regarding their impact on mortality and cardiovascular outcomes. Trial registration: PROSPERO (CRD: 42023446811).